Simulation of Ultrasonic Spray Pyrolysis Deposition Method by Finite Element Method - Pham, Phi Hung; Luong, Huu Bac; Cao, Xuan Quan (Old Journal, 2018)
The current paper introduces simulations results of The Ultrasonic spray pyrolysis technics by finite element method. In order to get the optimal uniformity of deposited film on the substrate The technology parameters such as carried gas pressure, solution pump speed and distance from substrate to spray nozzle were varied. The study results showed that the optimal calculated pressure of carrier gas flow are from 60 lb/in² to 80 lb/in², the distance from substrate to spray nozzle are from 13 cm to 15 cm and solution pump speed smaller than 1.5 ml/min. The results obtained from experiments are compared with the simulated results and found to be similar to each other.